Pyramidal microwave absorbers: leveraging ceramic materials for improved electromagnetic interference shielding - Rosli, Nur Shafikah; Abdullah, Hasnain; Kasim, Linda Mohd; Abdullah, Samihah; Taib, Mohd Nasir; Kasim, Shafaq Mardhiyana Mohamat; Noor, Norhayati Mohd; Ahmad, Azizah (Institute of Advanced Engineering and Science, 2025)
This study presents the development and optimization of pyramidal microwave absorbers designed for efficient electromagnetic interference (EMI) reduction in anechoic chambers. Based on prior research, this work transitions from conventional flat cement-carbon absorbers to a novel pyramidal design, incorporating silicon carbide (SiC) as ceramic materials. Introducing ceramic materials into the cement-carbon composite aims to enhance absorption across a broader frequency range while maintaining structural integrity. The study evaluates five sets of pyramidal absorbers with varying SiC content within the 1–12 GHz frequency range. Reflectivity performance was assessed using the naval research laboratory (NRL) Arch free space method at a 0° incidence angle. Among the tested absorbers, the set containing 10% SiC demonstrated superior performance, achieving minimum and maximum reflectivity values of -26.6215 and -55.2752 dB, respectively, particularly in the C-band. The findings highlight the significant impact of material composition and porosity on the absorber's effectiveness, providing valuable insights for the future design of high-performance EMI absorbers.